2004
DOI: 10.1515/bot.2004.019
|View full text |Cite
|
Sign up to set email alerts
|

Dinoflagellate cysts in recent marine sediments from the east coast of Russia

Abstract: Forty-two different dinoflagellate cyst types were found in recent sediment samples collected between July 1999-September 2002 from 44 stations along the eastern coast of Russia. This represents the first survey of recent dinoflagellate cysts in Russian marine waters. Forty cysts were identified to the species level, representing 17 genera. The most common cysts were those of ellipsoidal Alexandrium spp., Protoceratium reticulatum, Gonyaulax spp., Polykrikos kofoidii, P. schwartzii, Protoperidinium americanum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 49 publications
3
37
1
1
Order By: Relevance
“…The motile stage of P. reticulatum has a wide geographical distribution that comprises global coastal waters including the North Sea and the Baltic Sea, and the Mexican Pacific, the Gulf of Mexico, the Atlantic coast of North America, the east coast of Russia, New Zealand and South Africa, among other areas (e.g. Braarud, 1945;Reinecke, 1967;Steidinger and Williams, 1970;Herná ndez-Becerril, 1988;Hansen et al, 1996Hansen et al, /1997MacKenzie et al, 1998;Hä llfors, 2004;Kim et al, 2004;Orlova et al, 2004). In South America, the species has been recorded in coastal waters of Argentina, Chile and Brazil (see Balech, 1988;Seguel et al, 2005;Odebrecht, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The motile stage of P. reticulatum has a wide geographical distribution that comprises global coastal waters including the North Sea and the Baltic Sea, and the Mexican Pacific, the Gulf of Mexico, the Atlantic coast of North America, the east coast of Russia, New Zealand and South Africa, among other areas (e.g. Braarud, 1945;Reinecke, 1967;Steidinger and Williams, 1970;Herná ndez-Becerril, 1988;Hansen et al, 1996Hansen et al, /1997MacKenzie et al, 1998;Hä llfors, 2004;Kim et al, 2004;Orlova et al, 2004). In South America, the species has been recorded in coastal waters of Argentina, Chile and Brazil (see Balech, 1988;Seguel et al, 2005;Odebrecht, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, surface sediment samples collected simultaneously with plankton samples in Aniva Bay (Sea of Okhotsk) contained living cysts of Alexandrium cf. minutum [19]. A more precise identification of those cysts was not possible as they did not germinate.…”
Section: Resultsmentioning
confidence: 99%
“…Given the vast morphological differences reported for Cochlodinium cysts in sediments (6,(29)(30)(31)(32)(33)(34) and in culture (10,27,28) and the need to create maps of these cyst beds for fishery management (among other) purposes, the development of an accurate (40) detected C. polykrikoides in sediment samples using real-time PCR, the detection of vegetative cells or DNA residues of vegetative cells could not be excluded. The newly developed FISH assay reported here combines molecular and microscopic methods to ensure the accurate identification of C. polykrikoides resting cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies have reported the identification of resting cysts of C. polykrikoides or Cochlodinium sp. from sediments (6,(29)(30)(31)(32)(33)(34), but these studies have generally identified the cysts using previously published micrographs from Fukuyo (35) …”
mentioning
confidence: 99%